The Effect of Entrepreneurial Orientation on SME Performance: The Role of Social Media Usage and Absorptive Capacity - Ardiles, Ardiles; Yasri, Yasri (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study investigates the impact of entrepreneurial orientation on SME performance mediated by social media usage and absorptive capacity. Data were collected from 410 SME owners in Solok City using stratified random sampling based on six industrial sectors and analyzed with SmartPLS 4.0. The results show that entrepreneurial orientation has a positive effect on SME performance, with social media use and absorption capacity acting as significant mediators. These findings indicate that SMEs should prioritize entrepreneurial behavior, social media usage, and absorption capacity in improving performance. This study contributes to the literature on SME performance by examining six industrial sectors that adopt and utilize social media usage and absorption capacity in mediating entrepreneurial orientation on SME performance.